Neurobiological outcomes of cognitive behavioral therapy for obsessive-compulsive disorder: A systematic review - Poli, Andrea; Pozza, Andrea; Orrù, Graziella; Conversano, Ciro; Ciacchini, Rebecca; Pugi, Daniele; Angelo, Nicole Loren; Angeletti, Lorenzo Lucherini; Miccoli, Mario; Gemignani, Angelo (Frontiers in Psychiatry, 2022)
Introduction. Obsessive-compulsive disorder (OCD) is characterized by recurrent distressing thoughts and repetitive behaviors, or mental rituals performed to reduce anxiety. Recent neurobiological techniques have been particularly convincing in suggesting that cortico-striatal-thalamic-cortico (CSTC) circuits, including orbitofrontal cortex (OFC) and striatum regions (caudate nucleus and putamen), are responsible for mediation of OCD symptoms. However, it is still unclear how these regions are affected by OCD treatments in adult patients. To address this yet open question, we conducted a systematic review of all studies examining neurobiological changes before and after first-line OCD psychological treatment, i.e., cognitive-behavioral therapy (CBT). Methods. Studies were included if they were conducted in adults with OCD and they assessed the neurobiological effects of CBT before and after treatment. Two databases were searched: PsycINFO and PubMed for the time frame up to May 2022. Results. We obtained 26 pre-post CBT treatment studies performed using different neurobiological techniques, namely functional magnetic resonance imaging (fMRI), Positron Emission Tomography (PET), regional Cerebral Blood Flow (rCBF), 5-HT concentration, Magnetic Resonance Imaging (MRI), Magnetic Resonance Spectroscopy (MRS), Electroencephalography (EEG). Neurobiological data show the following after CBT intervention: i) reduced activations in OFC across fMRI, EEG and rCBF; ii) decreased activity in striatum regions across fMRI, rCBF, PET and MRI; iii) increased activations in cerebellum (CER) across fMRI and MRI; iv) enhanced neurochemical concentrations in MRS studies in OFC, anterior cingulate cortex (ACC) and striatum regions. Most of these neurobiological changes are also accompanied by an improvement in symptom severity as assessed by a reduction in Y-BOCS scores. Conclusions. CBT seems to be able to restructure, modify and transform the neurobiological component of OCD, in addition to the clinical symptoms. Nevertheless, further studies are necessary to frame the OCD spectrum in a dimensional way.